"To Give Good Science": Doing Qualitative Research in the Afterward - Patti Lather (Arizona State University, 2014)
This article explores the "afterward" for qualitative research in the ruins of NCLB and its failure to deliver. In the space opened up "after" the dominance of the gold standard bullying and "metric mania" of neo-positivism, I articulate a post-retirement project on the weight of sports in U.S. secondary schools out of a re-engagement with the work of Walter Benjamin.  Here my interest is to imagine forward out of troubling the narrow scientism of the recent past of educational research toward a post-qualitative future.